IMPLEMENTASI UDL DALAM MICRO LEARNING: PEMBELAJARAN BIOLOGI INKLUSIF UNTUK LITERASI SAINS DAN BERPIKIR MATEMATIS - Ni Nyoman Parmithi (SEMBIO: Prosiding Seminar Nasional Biologi dan Pendidikan Biologi, 2026)
Learning transformation in the digital age requires adaptive, flexible, and inclusive learning strategies. One relevant approach is Universal Design for Learning (UDL) combined with micro learning as a small unit and modular-based learning strategy. This study aims to describe the implementation of UDL in micro learning in inclusive biology learning and analyze its impact on students' science literacy and mathematical thinking skills. The study used a mixed methods approach with an embedded design. The research subjects were students in inclusive classes at the secondary school level. Data were collected through science literacy tests, mathematical thinking tests, observations, questionnaires, and interviews. The results showed that the implementation of UDL in micro learning was able to improve students' science literacy and mathematical thinking, especially for students with special needs, as well as provide a more meaningful and accessible learning experience.